Avaliação de um sistema adesivo universal utilizado como selante de fossas e fissuras - Botton, Graziela (2018)
This work is composed by two studies, whose main theme is the use of adhesive systems in pit and fissures sealants application technique. Manuscript 1: Are self-etch adhesive systems effective in the retention of occlusal sealants? A systematic review and meta-analysis. The aim of this study was to systematically review the literature of randomized clinical trials found in PUBMED/MEDLINE, CENTRAL and ClinicalTrials.gov databases up to June 2015 to establish whether there is a difference between the retention rates throughout time of occlusal sealants applied with self-etch adhesive systems or with prior acid etching, with or without the use of adhesive systems. From 683 potentially eligible studies, 10 were selected for full-text analysis and 5 were included in the meta-analysis. Statistically significant difference was found favoring the acid etching group. This study elucidated that the retention throughout time of pit and fissure sealants is higher when the application is in the conventional mode, with prior acid etching of the enamel, regardless of the use of adhesive system. No study included in this systematic review evaluated universal adhesive systems. Manuscript 2: Universal adhesive system in self-etch mode may not be a valid option for bonding resin-based fissure sealants. This study evaluated the microshear bond strength (μSBS) of the Scothbond Universal adhesive system (SBU) applied in self-etch mode combined with the resin-based sealant FluroShield (FLSH) or as a single material and also evaluated the SBU and FLSH water sorption and solubility. Forty-two third molars were randomly assigned in 6 groups (n = 7) according to a) enamel condition: sound or demineralized and b) material: SBU+FLSH, SBU and FLSH. The μSBS data were analyzed using two-way ANOVA and Tukey test (α=0.05). The FLSH applied in conventional mode, with prior acid etching, showed higher bond strength values and there was no difference in enamel condition. Sorption and solubility were evaluated according to ISO 4049:2009. Ten disk shaped specimens were prepared of each material (SBU and FLSH). Each disk was tested separately. At first, they were stored in a desiccator, after they were immersed in distilled water, so they were desiccated again. Specimens disk were weighed daily until achieving constant mass in each one of these three steps descripted above (m1, m2 and m3). The data were analyzed by the Mann-Whitney U test to assess the differences in average water sorption, solubility and real % absorbed water (SPc%) between the materials. SBU showed higher averages of water sorption and solubility and SPc% was almost five times higher than FLSH. Thus, universal adhesive system in self-etch mode is not a valid option for the use combined of pit and fissure sealants or as a sealant itself, because it shows lower bond strength to the enamel and it undergoes greater damage when exposed to water. It is suggested as the best strategy for the application of pit and fissure sealants, the prior acid conditioning of the enamel.